2021
DOI: 10.1016/j.worlddev.2020.105235
|View full text |Cite
|
Sign up to set email alerts
|

Towards a political economy of the COVID-19 crisis: Reflections on an agenda for research and action

Abstract: The spread of COVID-19 has raised difficult questions that interrogate the pandemic as a public health emergency, an economic crisis and a disruptor of consolidated governance forms. While addressing the public health emergency must be the main priority, we also need to track the ways in which the crisis is reconfiguring economic and political ordering and diverse actors are renegotiating relations in the exceptional circumstances the pandemic has created. These dimensions can have far-reaching implications in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 14 publications
1
12
0
3
Order By: Relevance
“…There has been a lot of concern and speculation, in South Africa and internationally, about how the Covid-19 pandemic will impact on food systems, agriculture, land rights and food security (Cotula 2021;FAO et al 2020;PLAAS 2020;Schmidhuber 2020). As the pandemic conditions have continued it has become clear from various surveys that indeed there are increasing levels of food and nutrition insecurity in South Africa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a lot of concern and speculation, in South Africa and internationally, about how the Covid-19 pandemic will impact on food systems, agriculture, land rights and food security (Cotula 2021;FAO et al 2020;PLAAS 2020;Schmidhuber 2020). As the pandemic conditions have continued it has become clear from various surveys that indeed there are increasing levels of food and nutrition insecurity in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the development of small-and medium-scale market-orientated black commercial farmers can make the greatest contribution to a more equitable agricultural sector and much needed employment creation (Cousins 2015;NPC 2011). Covid-19 has already been seen to pose a threat to this as, among other impacts, it may undermine the ability of small-scale farmers to sell their produce, potentially affecting farm viability and leading to distress sales of land (Cotula 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Atalan (2020) considera que las medidas que han tomado los países para afrontar la pandemia tales como aislamiento social, cierre de comercios y vuelos, además de despido de personas de sus empleos, traen un desastre económico sin precedentes. A medida que el COVID-19 se extendió por prácticamente todo el mundo ha puesto al descubierto la debilidad de un sistema económico mundial agravando las desigualdades estructurales a nivel local y global (Cotula, 2021).…”
Section: Acciones Financierasunclassified
“…No paper published in 2020 or 2021 is without a reference to the global pandemic and its major psychosocial, economic, public health, political, and higher education impacts ( Usher et al, 2020 ; Cotula, 2021 ; Jackson, 2021 ; Khalil et al, 2021 ; Lynch and Bambra, 2021 ). Society changed unexpectedly and profoundly in response to the global pandemic.…”
Section: Introductionmentioning
confidence: 99%